Findbuch des Bestandes Abt. 11 Regierungskanzlei (Obergericht) zu Glückstadt - Rathjen, Jörg (Veröffentlichungen des Landesarchivs Schleswig-Holstein, 2020)
The chancellery was established as the supreme judicial and administrative authority for the royal portion of Schleswig and Holstein in Flensburg in 1648 and moved to Glückstadt in 1649. Its jurisdiction had been limited to Holstein since 1713 and was extended to the county of Rantzau in 1734, to the Plönian lands in 1762 and to the Gottorfian lands in 1774. At the same time, the name "Glückstädtische Regierung" was replaced by "Holsteinische Landesregierung zu Glückstadt und Holsteinisches Oberkonsistorium". The previously formally different special courts - judicial chancellery, Oberamtsgericht, Pinnebergisches-, Altonaisches-, Rantzauisches Oberappellationsgericht - were combined in 1806 as "Holsteinisches Obergericht". Since 1816 it was called "Holstein-Lauenburgisches Obergericht". When justice and administration were separated in the middle instance in 1834, the administration was transferred to the Schleswig-Holstein government at Gottorf; the higher court continued to exist as a purely judicial authority. When the judiciary and administration were separated in 1834, the records were divided. Most of the judicial files remaining in Glückstadt were later destroyed; the administrative files were preserved and form the core of the holdings kept in the Schleswig-Holstein State Archives.